2003
DOI: 10.1183/09031936.03.00051303
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor family genes in a phenotype of COPD associated with emphysema

Abstract: Genetic factors are believed to play a role in the individual susceptibility to chronic obstructive pulmonary disease (COPD). Tumour necrosis factor (TNF) family genes have been widely investigated but inconsistent results may lie either in the genetic heterogeneity of populations or in the poor phenotype definition. A genetic study was performed using a narrower phenotype of COPD.The authors studied 86 healthy smokers and 63 COPD subjects who were enrolled based on irreversible airflow obstruction (forced exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 47 publications
(62 reference statements)
2
27
1
1
Order By: Relevance
“…A TNF-α gene polymorphism resulting in increased TNF-α levels has also been described in a population that is uniquely susceptible to the development of COPD (Huang et al 1997;Sakao et al 2002), although other studies have not been able to corroborate this fi nding (Higham et al 2000;Ferrarotti et al 2003). Interestingly, serum concentrations of TNF-α, as well as TNF-α secretion by monocytes, is particularly robust in the subset of COPD patients with weight loss or cachexia (Di Francia et al 1994;De Godoy et al 1996;Pitsiou et al 2002).…”
Section: Tumor Necrosis Factor-alpha (Tnf-α)mentioning
confidence: 85%
“…A TNF-α gene polymorphism resulting in increased TNF-α levels has also been described in a population that is uniquely susceptible to the development of COPD (Huang et al 1997;Sakao et al 2002), although other studies have not been able to corroborate this fi nding (Higham et al 2000;Ferrarotti et al 2003). Interestingly, serum concentrations of TNF-α, as well as TNF-α secretion by monocytes, is particularly robust in the subset of COPD patients with weight loss or cachexia (Di Francia et al 1994;De Godoy et al 1996;Pitsiou et al 2002).…”
Section: Tumor Necrosis Factor-alpha (Tnf-α)mentioning
confidence: 85%
“…A study investigating the -308G/A polymorphism in the TNF-α gene, the LtαNcoI polymorphism in the Lt-α gene, the A/G polymorphism in the TNFR1 gene, and the M/R polymorphism in the TNFR2 gene, did not yield any association between these polymorphisms and a risk for COPD (Ferrarotti et al 2003). The uncertainty regarding the relationship between the TNF-308G/A polymorphism and TNF-α expression in vivo as well as the possibility of another TNF gene polymorphism of greater functional significance in COPD also need to be considered (Higham et al 2000;Ferrarotti et al 2003).…”
Section: Gene Polymorphisms Of Inflammatory Mediators In Relation To mentioning
confidence: 99%
“…There was no association between the TNF-α gene promoter genotype and the severity of airflow obstruction or the degree of emphysema in COPD (Higham et al 2000), neither this genotype played a significant role in bronchiectasis developing as a consequence of frequent respiratory tract infections in COPD patients (Patuzzo et al 2000). A study investigating the -308G/A polymorphism in the TNF-α gene, the LtαNcoI polymorphism in the Lt-α gene, the A/G polymorphism in the TNFR1 gene, and the M/R polymorphism in the TNFR2 gene, did not yield any association between these polymorphisms and a risk for COPD (Ferrarotti et al 2003). The uncertainty regarding the relationship between the TNF-308G/A polymorphism and TNF-α expression in vivo as well as the possibility of another TNF gene polymorphism of greater functional significance in COPD also need to be considered (Higham et al 2000;Ferrarotti et al 2003).…”
Section: Gene Polymorphisms Of Inflammatory Mediators In Relation To mentioning
confidence: 99%
See 1 more Smart Citation
“…One study compared gene polymorphism in 169 Dutch COPD patients compared with Dutch controls, and reported an increased frequency of the G/A genotype in patients without radiological emphysema (Kucukaycan, M., et al, 2002). Another study from Italy compared 63 male patients with COPD with 86 healthy controls, and found no difference in gene polymorphisms between the two groups (Ferrarotti, I., et al, 2003).…”
Section: Role Of Inflammatory Mediators and Cytokines In Protease-antmentioning
confidence: 99%